PROTECTION OF THE WEAKER PARTNER IN THE MARITAL PROPERTY AGREEMENTS - Kovaček Stanić, Gordana; Samardžić, Sandra M. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
In many jurisdictions, spouses/common-law partners can choose which matrimonial property regime they want to be applied on their property relations. Viewed comparatively, such freedom exists in Western European countries for some time, but recently, both Eastern and Central European countries introduced the possibility of concluding marital property agreement in their legal systems, which changes the default marital property regime. However, the spouses do not have an absolute freedom when concluding such a contract. Restriction of freedom is due to the fact that the contracting parties are specific subjects - married persons, between whom exists personal relationships, which requires caution and some sort of protection of the weaker partner. This paper analyzes the legal mechanisms to protect weaker partners in domestic family law and in a comparative European law.